Circulating Dipeptidyl Peptidase Activity Is a Potential Biomarker for Inflammatory Bowel Disease. Issue 1 (19th January 2022) - Jaenisch, Simone E.; Abbott, Catherine A.; Gorrell, Mark D.; Bampton, Peter; Butler, Ross N.; Yazbeck, Roger
Abstract : INTRODUCTION: Dipeptidyl peptidase (DPP)-4 is part of a larger family of proteases referred to as DPPs. DPP4 has been suggested as a possible biomarker for inflammatory bowel disease (IBD). Circulating DPP4 (cDPP4) enzyme activity was investigated as a potential biomarker for IBD. In addition, DPP enzyme activity and gene expression were quantified in colonic tissue of patients with IBD and non-IBD. METHODS: In study 1, DPP enzyme activity was quantified in plasma samples from 220 patients with IBD (Crohn's disease [CD] n = 130 and ulcerative colitis [UC] n = 90) and non-IBD controls (n = 26) using a colorimetric assay. In study 2, tissue and plasma samples were collected from 26 patients with IBD and 20 non-IBD controls. Plasma C-reactive protein (CRP) was quantified in all patients. Colonic DPP4, DPP8, DPP9, and fibroblast activation protein (FAP) gene expression was determined by quantitative polymerase chain reaction. cDPP and cFAP enzyme activity was also measured. Sensitivity and specificity were determined by receiver operating characteristic curve analysis. RESULTS: In study 1, total cDPP activity was found to differentiate patients with CD with active disease (n = 18) from those in remission (n = 19; sensitivity 78% and specificity 63%). In study 2, total cDPP and cFAP activity was 28% and 48% lower in patients with elevated CRP (>10 mg/L), respectively, compared with patients with normal CRP. Gene expression of DPP4, FAP, and DPP8 was also significantly higher in colonic biopsies from patients with IBD compared with non-IBD patients ( P < 0.05). DISCUSSION: Our findings implicate the DPP enzyme family in intestinal inflammation and suggest future biomarker applications to differentiate the pathophysiological aspects of IBD.